FR4 copper-clad plate glue solution, FR4 copper-clad plate and preparation method of FR4 copper-clad plate glue solution
By using arylacetylene resin and other resin combinations, the resin ratio and group distribution ratio are adjusted to prepare FR4 copper clad liquor with low dielectric constant and dielectric loss, solving the problem that existing electronic materials cannot meet the needs of low dielectric constant and low dielectric loss, and achieving the excellent comprehensive performance required by electronic components with high frequency and high-speed signal transmission.
Patent Information
- Application Number
- CN202411507338.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-28
AI Technical Summary
Existing electronic materials cannot meet the needs of low dielectric constant and low dielectric loss, and it is difficult to adapt to the development of electronic components with high frequency and high-speed signal transmission.
A aryl acetylene resin is used as the main resin, combined with polyimide resin, furan resin and dicyclopentadiene epoxy resin, and a low dielectric constant and dielectric loss FR4 copper clad liquor is prepared by adjusting the resin ratio and the component distribution ratio, and copper clad plate is made by a specific preparation method.
The obtained copper clad plate has achieved a dielectric constant of less than 3.1, a dielectric loss of less than 0.003, high thermosetting, flame retardant reaching FV-0 level, excellent peel strength, and significantly improved overall performance.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper clad laminates, and in particular to an FR4 copper clad laminate glue, an FR4 copper clad laminate and a preparation method thereof. Background Art
[0002] As electronic components are developing towards small, light, thin, high-performance and multifunctionality, high-frequency and high-speed signal transmission is brought about. This requires the dielectric constant and dielectric loss of electronic materials to be relatively low, but existing electronic materials cannot meet the requirements of lower dielectric constant and lower dielectric loss. Therefore, it is particularly important to develop copper clad laminates with low dielectric constant and low dielectric loss. Summary of the invention
[0003] In order to solve the above technical problems existing in the prior art, the present invention provides an FR4 copper clad laminate adhesive, an FR4 copper clad laminate and a preparation method thereof.
[0004] The technical solution of the present invention to solve the above technical problems is as follows:
[0005] The first aspect of the present invention is to provide an FR4 copper clad laminate adhesive, comprising a resin, a curing agent, a catalyst, a filler and a solvent; wherein the resin comprises an aromatic acetylene resin.
[0006] The FR4 copper clad laminate glue provided by the invention adopts arylacetylene resin as the main resin and is used in combination with other components, thereby reducing the dielectric constant and dielectric loss of the prepared copper clad laminate.
[0007] On the basis of the above technical solution, the present invention can also make the following technical improvements:
[0008] Furthermore, the resin also includes polyimide resin, furan resin, and dicyclopentadiene epoxy resin.
[0009] The beneficial effect of adopting the above further technical solution is that: by adding polyimide resin, furan resin and dicyclopentadiene epoxy resin, the resin ratio is increased, thereby further reducing the dielectric constant and dielectric loss of the prepared copper clad laminate and increasing the thermosetting property.
[0010] Furthermore, the following components are included in parts by weight: 35-45 parts of aromatic acetylene resin, 13-25 parts of polyimide resin, 10-15 parts of furan resin, 15-27 parts of dicyclopentadiene epoxy resin, 0.2-0.5 parts of curing agent, 40-74 parts of solvent, 0.17-0.28 parts of catalyst and 19-28 parts of filler.
[0011] The beneficial effect of adopting the above further technical solution is that the dielectric constant and dielectric loss of the prepared copper clad laminate can be further reduced by adjusting and matching the proportions of the components.
[0012] Furthermore, the curing agent is triethanolamine, the catalyst is imidazole, the filler includes alumina and silicon powder, and the solvent includes sulfolane and toluene.
[0013] The beneficial effect of adopting the above further technical solution is that the emulsified resin is completely dissolved to obtain the glue solution by adding toluene, cyclopentane solvent, triethanolamine curing agent, imidazole, aluminum oxide and silicon powder.
[0014] Furthermore, the FR4 copper clad laminate adhesive comprises 15 to 26 parts of toluene and 15 to 26 parts of sulfolane, in parts by weight.
[0015] The second aspect of the present invention is to provide a method for preparing an FR4 copper clad laminate using the above-mentioned FR4 copper clad laminate glue, comprising the following steps:
[0016] (1) preparing glue solution: weighing each component according to weight, dissolving, mixing and emulsifying to obtain glue solution;
[0017] (2) impregnating the glass fiber cloth with the adhesive obtained in step (1), and drying the cloth to obtain a prepreg;
[0018] (3) Covering the prepreg obtained in step (2) with copper foil and pressing it together to obtain the FR4 copper clad laminate.
[0019] Further, step (1) includes the following steps:
[0020] S1. Weigh the aromatic acetylene resin, polyimide resin, furan resin, dicyclopentadiene epoxy resin, curing agent and the first part of the solvent according to weight proportions, and mix and stir until they are completely dissolved;
[0021] S2, weigh the catalyst according to weight, add it to the mixed solution of S1, and stir until it is completely dissolved;
[0022] S3, weigh the filler according to the weight, add it to the mixed solution of S2, stir and emulsify;
[0023] S4. Weigh the second part of the solvent according to the weight percentage and add it to the mixed solution of S3, stir evenly, and obtain a glue solution.
[0024] Furthermore, the weight percentage of the first part of the solvent is 30 to 52 parts, and the weight percentage of the second part of the solvent is 10 to 22 parts.
[0025] Furthermore, in parts by weight, the first part of the solvent comprises 15 to 26 parts of toluene solvent and 15 to 26 parts of sulfolane solvent, and the second part of the solvent comprises 5 to 11 parts of sulfolane solvent and 5 to 11 parts of toluene solvent.
[0026] The beneficial effect of adopting the above further technical solution is that the solvent is added in two parts, the first part of the solvent is used to fully dissolve the components, and the second part of the solvent is used to adjust the viscosity of the mixed solution and make the mixed solution fully mixed, so as to obtain a uniform and stable glue solution.
[0027] Furthermore, in step (1), the gelling time of the glue solution is 280 to 320 seconds; in step (2), the drying treatment is drying in an oven at 180 to 190° C. for 3 to 5 minutes, and the glue content of the prepreg is 47 to 56%.
[0028] The beneficial effect of adopting the above further technical solution is that the glue is evenly distributed on the glass fiber cloth, and after drying, the obtained prepreg has a uniform appearance.
[0029] Furthermore, in step (3), several semi-cured sheets are stacked in sequence, covered with copper foil on both sides, and then controlled at a pressure of 5 to 17 MPa and a temperature of 160 to 210° C. in a vacuum press, hot pressed for 2 to 4 hours, and kept warm for 1 to 3 hours to obtain a FR4 copper clad laminate.
[0030] The beneficial effect of adopting the above further technical solution is that: after the above pressing process, a copper clad laminate is manufactured, and the copper clad laminate has excellent comprehensive performance.
[0031] Another aspect of the present invention is to provide a FR4 copper clad laminate, which is prepared by the above-mentioned preparation method of the FR4 copper clad laminate.
[0032] Compared with the prior art, the present invention has the following technical effects:
[0033] (1) The present invention uses arylacetylene resin as the main resin, and adds polyimide resin, furan resin, and dicyclopentadiene epoxy resin to increase the resin ratio, thereby increasing the thermosetting property and reducing the dielectric constant and dielectric loss;
[0034] (2) The components of the resin glue of the present invention are combined, and the performance of the copper clad laminate is improved by using an aromatic acetylene resin, a curing agent, a catalyst, a solvent, and a filler for preparation.
[0035] (3) The copper clad laminate provided by the present invention has a dielectric constant of <3.1, a dielectric loss (10G) of <0.003, a Tg of >210°C, a T288 of >120 minutes, a flame retardancy of FV-0, a peel strength of >0.90N / mm, and excellent comprehensive performance. DETAILED DESCRIPTION
[0036] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may extend based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0037] Example 1
[0038] A method for preparing a low-dielectric and low-loss FR4 copper-clad laminate comprises the following steps:
[0039] (1) At room temperature, 35 parts by weight of arylacetylene resin, 13 parts by weight of polyimide resin, 10 parts by weight of furan resin, 15 parts by weight of dicyclopentadiene epoxy resin, 0.2 parts by weight of triethanolamine curing agent, 15 parts by weight of toluene solvent, and 15 parts by weight of sulfolane solvent are added into a container and stirred to fully dissolve;
[0040] (2) at room temperature, 0.17 parts by weight of imidazole was added to the mixed solution of step (1) and stirred to fully dissolve it;
[0041] (3) Add 8 parts of aluminum oxide and 11 parts of silicon powder by weight to the mixed solution of step (2) and stir evenly to fully emulsify;
[0042] (4) adding 5 parts of sulfolane solvent and 5 parts of toluene solvent to the mixed solution of step (3) by weight and stirring evenly to obtain a glue solution; the gelling time of the glue solution is 320 seconds, and the glue solution is uniform and stable;
[0043] (5) evenly distributing the adhesive obtained in step (4) on Low DK glass fiber cloth (low dielectric glass fiber cloth), and baking in an oven at 185° C. for 5 min to obtain a prepreg; the prepreg has a uniform appearance and a glue content of 47%;
[0044] (6) Stack 6 prepregs prepared in step (5) as required, cover both sides with 18-micron copper foil, and hot-press for 3 h and keep warm for 2 h in a vacuum press at a pressure of 5 MPa and a temperature of 160° C. to obtain a copper-clad laminate.
[0045] Example 2
[0046] A method for preparing a low-dielectric and low-loss FR4 copper-clad laminate comprises the following steps:
[0047] (1) At room temperature, 39 parts by weight of arylacetylene resin, 17 parts by weight of polyimide resin, 13 parts by weight of furan resin, 20 parts by weight of dicyclopentadiene epoxy resin, 0.3 parts by weight of triethanolamine curing agent, 17 parts by weight of toluene solvent, and 17 parts by weight of sulfolane solvent are added to a container and stirred to fully dissolve;
[0048] (2) at room temperature, 0.22 parts by weight of imidazole was added to the mixed solution of step (1) and stirred to fully dissolve it;
[0049] (3) Add 10 parts of aluminum oxide and 14 parts of silicon powder by weight to the mixed solution of step (2) and stir evenly to fully emulsify;
[0050] (4) adding 7 parts of sulfolane solvent and 7 parts of toluene solvent to the mixed solution of step (3) by weight and stirring evenly to obtain a glue solution; the gelling time of the glue solution was 293 s, and the glue solution was uniform and stable;
[0051] (5) The glue obtained in step (4) is evenly distributed on the Low DK glass fiber cloth, and baked in an oven at 185° C. for 3.5 min to obtain a prepreg; the prepreg has a uniform appearance and a glue content of 53%;
[0052] (6) Stack 6 prepregs prepared in step (5) as required, cover both sides with 18-micron copper foil, and hot-press for 3 h and keep warm for 2 h in a vacuum press at a pressure of 12 MPa and a temperature of 180° C. to obtain a copper-clad laminate.
[0053] Example 3
[0054] A method for preparing a low-dielectric and low-loss FR4 copper-clad laminate comprises the following steps:
[0055] (1) At room temperature, 44 parts by weight of arylacetylene resin, 25 parts by weight of polyimide resin, 15 parts by weight of furan resin, 25 parts by weight of dicyclopentadiene epoxy resin, 0.4 parts by weight of triethanolamine curing agent, 25 parts by weight of toluene solvent, and 25 parts by weight of sulfolane solvent are added to a container and stirred to fully dissolve;
[0056] (2) at room temperature, add 0.25 parts by weight of imidazole to the mixed solution of step (1) and stir to fully dissolve it;
[0057] (3) Add 12 parts of aluminum oxide and 16 parts of silicon powder by weight to the mixed solution of step (2) and stir evenly to fully emulsify;
[0058] (4) adding 11 parts of sulfolane solvent and 11 parts of toluene solvent to the mixed solution of step (3) by weight and stirring evenly to obtain a glue solution; the gelling time of the glue solution is 280 seconds, and the glue solution is uniform and stable;
[0059] (5) The adhesive obtained in step (4) is evenly distributed on the Low DK glass fiber cloth, and baked in an oven at 185° C. for 3 min to obtain a prepreg; the prepreg has a uniform appearance and a glue content of 55%.
[0060] (6) Stack 6 prepregs prepared in step (5) as required, cover both sides with 18-micron copper foil, and perform hot pressing for 3 h and heat preservation for 2 h in a vacuum press under a pressure of 17 MPa and a temperature of 210° C. to obtain a copper clad laminate.
[0061] Comparative Example
[0062] A method for preparing a copper clad laminate comprises the following steps:
[0063] (1) Weighing the following components of the adhesive solution in parts by weight: 53 parts of a polyimide resin, 30 parts of a bisphenol A epoxy resin, 0.2 parts of a dicyandiamide curing agent, 45 parts of a toluene solvent, 0.03 parts of imidazole, and 45 parts of an aluminum oxide filler, and mixing and stirring the components to obtain an adhesive solution;
[0064] (2) The glue obtained in step (1) is completely and evenly impregnated with ordinary glass fiber cloth, and then baked in an oven at 200° C. for 5 min to obtain a prepreg with a glue content of 54%;
[0065] (3) Stack 6 prepregs prepared in step (2) as required, cover both sides with 18-micron copper foil, and hot-press in a vacuum press at a pressure of 5 MPa and a temperature of 150° C. for 1.5 h to obtain a copper-clad laminate.
[0066] Test method description:
[0067] (1) Dielectric constant: GB / T 4722-2017-8.5;
[0068] (2) Dielectric loss (10G): GB / T 4722-2017-8.5;
[0069] (3)Tg(DSC): GB / T 4722-2017-6.7.1;
[0070] (4)T288: GB / T 4722-2017-6.11;
[0071] (5) Peel strength (N / mm): GB / T 4722-2017-7.2.1;
[0072] (6) Flame retardancy: GB / T 4722-2017-6.4.1;
[0073] The test data of each embodiment and comparative example are shown in Table 1.
[0074] Table 1 Test data of each embodiment and comparative example
[0075] Test items Example 1 Example 2 Example 3 Comparative Example Dielectric constant 2.83 2.88 3.03 4.19 Dielectric loss (10G) 0.0022 0.0025 0.0021 0.0079 Tg(DSC) / ℃ 215 214 211 163 T288 / min >120 >120 >120 63 Peel strength N / mm 0.97 1.03 1.05 0.65 Flame retardant FV-0 FV-0 FV-0 FV-0
[0076] By comparing the test experimental data in Table 1, it can be seen that the dielectric constant of the copper clad laminate of the embodiment is <3.0, the dielectric loss (10G) is <0.003, Tg>210°C, T288>120 minutes, the flame retardancy reaches FV-0 level, and the peel strength is >0.90N / mm.
[0077] Compared with Comparative Example 1, the dielectric constant, dielectric loss, Tg and other indicators of Examples 1-3 are significantly improved, and other basic indicators of Examples 1-3 are also better than those of Comparative Example 1. Therefore, the present invention provides a new high-frequency and high-speed copper clad laminate and a preparation method thereof. Compared with the existing copper clad laminate, the new copper clad laminate has a lower dielectric constant, low loss and high frequency compatibility, while other indicators are not reduced, and the comprehensive performance is excellent.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A FR4 copper clad laminate adhesive, characterized in that: The invention comprises resin, curing agent, catalyst, filler and solvent; wherein the resin comprises arylacetylene resin.
2. The FR4 copper clad laminate adhesive according to claim 1, characterized in that: The resin also includes polyimide resin, furan resin, and dicyclopentadiene epoxy resin.
3. The FR4 copper clad laminate adhesive according to claim 2, characterized in that: The invention comprises the following components in parts by weight: 35-45 parts of aromatic acetylene resin, 13-25 parts of polyimide resin, 10-15 parts of furan resin, 15-27 parts of dicyclopentadiene epoxy resin, 0.2-0.5 parts of curing agent, 40-74 parts of solvent, 0.17-0.28 parts of catalyst and 19-28 parts of filler.
4. The FR4 copper clad laminate adhesive according to any one of claims 1 to 3, characterized in that: The curing agent is triethanolamine, the catalyst is imidazole, the filler includes alumina and silicon powder, and the solvent includes sulfolane and toluene.
5. A method for preparing FR4 copper clad laminate using the FR4 copper clad laminate glue according to claim 3 or 4, characterized in that: The following steps are involved: (1) preparing glue solution: weighing each component according to weight, dissolving, mixing and emulsifying to obtain glue solution; (2) impregnating the glass fiber cloth with the adhesive obtained in step (1), and drying the cloth to obtain a prepreg; (3) Covering the prepreg obtained in step (2) with copper foil and pressing it together to obtain the FR4 copper clad laminate.
6. The method for preparing the FR4 copper clad laminate according to claim 5, characterized in that: Step (1) includes the following steps: S1. Weigh the aromatic acetylene resin, polyimide resin, furan resin, dicyclopentadiene epoxy resin, curing agent and the first part of the solvent according to weight proportions, and mix and stir until they are completely dissolved; S2, weigh the catalyst according to weight, add it to the mixed solution of S1, and stir until it is completely dissolved; S3, weigh the filler according to the weight, add it to the mixed solution of S2, stir and emulsify; S4. Weigh the second part of the solvent according to the weight percentage and add it to the mixed solution of S3, stir evenly, and obtain a glue solution.
7. The method for preparing the FR4 copper clad laminate according to claim 6, wherein: The weight proportion of the first part of the solvent is 30 to 52 parts, and the weight proportion of the second part of the solvent is 10 to 22 parts.
8. The method for preparing the FR4 copper clad laminate according to any one of claims 5 to 7, characterized in that: In step (1), the gelling time of the glue solution is 280 to 320 seconds; in step (2), the drying treatment is drying in an oven at 180 to 190° C. for 3 to 5 minutes, and the glue content of the prepreg is 47 to 56%.
9. The method for preparing the FR4 copper clad laminate according to any one of claims 5 to 7, characterized in that: In step (3), several semi-cured sheets are stacked in sequence, covered with copper foil on both sides, and then controlled at a pressure of 5 to 17 MPa and a temperature of 160 to 210° C. in a vacuum press, hot pressed for 2 to 4 hours, and kept warm for 1 to 3 hours to obtain a FR4 copper clad laminate.
10. A FR4 copper clad laminate, characterized in that: The FR4 copper clad laminate is prepared by the preparation method of any one of claims 5 to 9.
Citation Information
Patent Citations
Epoxy resin composition, and prepreg and laminated board with epoxy resin composition
CN105778430A
Phosphorus-containing active ester and halogen-free composition thereof, and copper-clad laminate
CN108250675A
Resin composition, prepreg for printed circuit and metal-coated laminate
US20210403659A1
Phosphorus-containing active ester, halogen-free composition and copper-clad foil substrate thereof
WO2018120564A1
Resin composition, prepreg used for printed circuit and metal-clad pressing plate
WO2019214000A1